Design of noise detection and warning in library reading room using Wemos D1 R2 Based on IoT - Sintawati, Andini; Windarti, Ira; Arrafi, Muhamad Dzammar (Institute of Computer Science (IOCS), 2023)
The library is one of the places needed by the community to improve academic knowledge, get information and become a means for students to learn. Library visitors certainly need a comfortable and quiet atmosphere so they can focus on reading books in the library. But not all visitors understand about the rules that apply to the library. Some visitors come just to chat, thus disturbing other visitors who are reading. Therefore, a system that can monitor the room is needed. The reading room noise detector aims to provide comfort and tranquility to visitors who come to read. the components used in this design are the Wemos D1 R2 microcontroller, DFRobot Analog Sound Sensor V2, DHT11, LCD, and Buzzer. This tool will work if the Sound Sensor detects Sound Intensity of more than 55dB then the Buzzer will be active and the LCD displays